Gnatoplasti tanpa Cangkok Tulang: Kasus Serial - Yuliastuti, Eka; Mangoenprawira, Ocky P.; Ismunandar, Adhe (Universitas Sam Ratulangi, 2026)
Abstract: Alveolar clefts are a group of cleft lip and/or palate disorders that can interfere with tooth growth, aesthetics, and oral function. Treatment is gradual and multidisciplinary, with initial procedures such as labioplasty and palatoplasty. However, postoperative facial bone growth disorders often occur. Gnathoplasty is generally performed with bone grafting, but this procedure carries a risk of complications. Therefore, gnathoplasty without bone grafting is starting to be considered as an alternative, especially in children under 10 years of age with a cleft width of ≤4 mm. This study aimed to discuss the clinical and esthetic outcomes of several cases of gnathoplasty without the use of bone grafts, and to assess the safety and effectiveness of the procedure. In this case study, there were three pediatric patients with similar clinical conditions and complaints underwent gnathoplasty without bone grafting using the mucosal tissue closure method at Santa Theresia Hospital in Jambi. Evaluation was conducted through clinical examination and pre- and post-operative photo documentation. The results showed that gnathoplasty without bone graft provided significant improvement in facial profile and patient esthetic satisfaction without complications. No post-operative infection was found. Healing was progressing well and recovery time was shorter. Post-operative hypernasality improved gradually without the need for speech therapy in the short term. In conclusion, gnatoplasty without bone grafting can be an appropriate treatment option in children with specific indications, as it provides good outcomes with low risk of complications. Keywords: gnathoplasty; bone graft; gnathoschizis Abstrak: Celah alveolar merupakan bagian dari kelainan celah bibir dan/atau langit-langit yang dapat mengganggu pertumbuhan gigi, estetika, dan fungsi rongga mulut. Penanganannya dilakukan secara bertahap dan multidisipliner melalui prosedur awal seperti labioplasti dan palatoplasti, namun gangguan pertumbuhan tulang wajah sering terjadi pascaoperasi. Gnatoplasti umumnya dilakukan dengan cangkok tulang, tetapi prosedur ini memiliki risiko komplikasi. Oleh karena itu, gnatoplasti tanpa cangkok tulang mulai dipertimbangkan sebagai alternatif, terutama pada anak di bawah usia 10 tahun dengan lebar celah ≤4 mm. Penulisan studi ini bertujuan untuk melaporkan hasil klinis dan estetika dari beberapa kasus gnatoplasti tanpa penggunaan cangkok tulang, serta menilai keamanan dan efektivitas prosedur tersebut. Dalam studi kasus ini, tiga pasien anak dengan kondisi klinis dan keluhan serupa menjalani gnatoplasti tanpa cangkok tulang menggunakan metode penutupan jaringan mukosa di Rumah Sakit SantaTheresia, Jambi. Evaluasi dilakukan melalui pemeriksaan klinis, dokumentasi foto pra dan pasca operasi. Hasil menunjukkan bahwa gnatoplasti tanpa cangkok tulang memberikan perbaikan bermakna pada profil wajah dan kepuasan estetika pasien tanpa komplikasi. Tidak ditemukan infeksi pasca operasi. Penyembuhan berjalan dengan baik dan waktu pemulihan lebih singkat. Hipernasalitas yang muncul pasca operasi membaik secara bertahap tanpa perlu terapi wicara dalam jangka pendek. Simpulan studi ini ialah gnatoplasti tanpa cangkok tulang pada anak dapat menjadi pilihan tindakan yang tepat sesuai indikasi dengan hasil yang baik dan berisiko rendah. Kata kunci: gnatoplasti; cangkok tulang: gnatoschizis